Riot Games’ Content Marketing Approach for VALORANT Champions 2022 - Edward Strazd (Press Start)
VALORANT is a competitive first-person shooter (FPS) game developed and released by Riot Games in 2020. The game has celebrated high player involvement in the competitive gaming scene wherein, only two years after the game’s release, the grand finals of the culminating event of 2022, VALORANT Champions 2022, peaked at 1.5 million viewers (Esports Charts, 2022a). Building on firsthand observation of following VALORANT Champions 2022 as it took place, this paper explores Riot Games’ content marketing approach for VALORANT Champions 2022, its impact on player engagement, and compares it with other esports marketing strategies. I analyze the main mediums of content distribution for the VALORANT Champions 2022 event (social media, website, and in-game content) and compare them against the content marketing sector using the latest developments in esports, with reference to competing game developers and esports organizations. I argue that Riot Games focuses on inclusivity of the global market, involving diverse types of players and regions, and their design/marketing choices create immersive experiences that incentivize players to be a part of the event in one form or another. The results suggest that other games with an esports scene could implement and expand content marketing, creating more themed experiences, similar to how Riot Games does with anthems, in-game content, and more, to grow and maintain interest in their competitive events.